OPPORTUNITIES AND CHALLENGES SHARIA BUSINESS INDUSTRY 5.0 IN INDONESIA - Kustiyah, Eny; Junaidi, Amir; Nurlaela, Siti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This research is important because various complex dynamics have occurred in governance planning for the development of management resources in the bureaucratic apparatus in Industry 5.0, ready to face technological advances and also able to pay attention to aspects of changes in people's lives in a sustainable manner. This research aims to analyze how the implementation of Industry 5.0 affects the Indonesian economic sector and the challenges faced in adopting this technology. Research method A comprehensive literature review was carried out to understand the Opportunities and Challenges of Sharia Business in Industry 5.0 and then applied in the Indonesian context. The findings of this research provide an explanation of the current conditions regarding Opportunities, Sharia Business Challenges in Industry 5.0, aspects such as digital infrastructure, workforce skills, and government policies that support or hinder the development of Industry 5.0 in Indonesia. The results of this research can provide input for policy and stakeholders in understanding the contribution of sharia business in Industry 5.0 to the Indonesian economy and formulating appropriate strategies to encourage sustainable economic growth. Keywords: Opportunities, Sharia Business Challenges in Industry 5.0